Pengaruh keterlibatan orang tua dalam pendidikan karakter di rumah terhadap perilaku siswa di sekolah - Ita'ufaidilah, Salvi (Maliki Interdisciplinary Journal, 2026)
This study discusses the influence of parental involvement in character education at home on students’ behavior at school. Character education is an essential aspect of shaping children into individuals with strong morals, ethics, discipline, and responsibility. The family serves as the first and primary environment in the process of character building before children enter the school environment. Through parenting patterns, role modeling, communication, and habituation of positive values at home, parents play a significant role in shaping children’s behavior. This study employs a literature review approach by analyzing various theories and previous studies related to character education, parental involvement, and student behavior at school. The findings indicate that active parental involvement in character education positively affects students’ behavior, including improved discipline, responsibility, politeness, and self-control within the school environment. Conversely, a lack of parental attention and guidance may lead to negative behavior in children. Furthermore, cooperation between parents and teachers is considered an important factor in maintaining consistency of character values implemented both at home and at school. Therefore, parental involvement has a significant influence on fostering positive student behavior in schools.